A coated modified positive electrode material and its preparation method and application

By using D-A type conjugated polymer to coat and modify the high-nickel positive electrode material to form a uniform and dense cladding layer, the problems of structural collapse and electrochemical performance deterioration of high-nickel positive electrode material under high temperature and high voltage conditions are solved, and the problem of structural collapse and electrochemical performance deterioration is achieved. Excellent magnification and circulation performance reduce safety hazards.

CN115939347BActive Publication Date: 2025-02-25GEM WUXI ENERGY MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211611384.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2025-02-25
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

During the battery operation cycle, especially under high temperature and high voltage conditions, high nickel positive electrode materials are prone to irreversible side reactions with the electrolyte, resulting in structural collapse and deterioration of electrochemical properties, and pose safety hazards.

Method used

The positive electrode material is coated and modified by D-A type conjugated polymer to form a uniform and dense coating layer, which enhances the chemical stability and conductivity of the material and slows down the volume effect during the charge and discharge process.

Benefits of technology

The rate performance and circulation performance of the positive electrode material are improved, the residual alkali content on the surface is reduced, the structural stability and conductive properties of the material are enhanced, and safety hazards are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115939347B_ABST
    Figure CN115939347B_ABST
Patent Text Reader

Abstract

The present invention relates to a coated modified positive electrode material and a preparation method and application thereof, wherein the preparation method comprises the following steps: mixing a D-A type conjugated polymer organic solution with a positive electrode material, removing the organic solvent, and obtaining the coated modified positive electrode material. The present invention uses a D-A type conjugated polymer to coat and modify the positive electrode material, and can form a uniform and dense coating layer on the surface of the material, and the thickness of the coating layer is controllable; moreover, the D-A type conjugated polymer has excellent chemical stability, and its good ductility can be used as a buffer matrix to slow down the volume effect of the charge and discharge process, and also has good conductivity; the coated modified positive electrode material of the present invention is used in a battery, which can make the battery have excellent rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries and relates to a positive electrode material, in particular to a coated modified positive electrode material and a preparation method and application thereof. Background Art

[0002] At present, the development of battery materials in the battery field is mainly concentrated in three major directions: high power, high energy and energy power. High-nickel materials have attracted attention due to their higher power performance. Among them, high-nickel positive electrode materials can be used in power tools, drones, digital markets and other products that require high-rate discharge. It has a wide application market and is one of the most promising development directions.

[0003] Ternary cathode materials have various unparalleled excellent properties, but as the nickel content of high-nickel cathode materials increases, the structural changes caused by the intrinsic defects of the high-nickel cathode materials greatly affect their electrical properties to a certain extent. A large amount of lithium-containing compounds such as Li2O or LiOH are easily generated on the surface of high-nickel cathode materials. Since they can react with HF in the electrolyte, there is also the problem of transition metal ion dissolution, which can easily cause the weakening of cycle performance and ultimately deteriorate the overall electrochemical performance.

[0004] In addition, during the battery working cycle, especially under high temperature and high voltage conditions, the high nickel cathode material is in direct contact with the electrolyte, which makes the oxidized Ni 4+ Irreversible side reactions occur with the electrolyte, causing structural collapse, and as the impedance of the material itself continues to increase, it may also cause serious safety problems.

[0005] In order to reduce the side reaction between high-nickel positive electrode materials and electrolytes, a common method is to coat the surface of the positive electrode materials with boron oxide or aluminum oxide. In addition, the surface of the high-nickel positive electrode material can also be coated with a conductive polymer, which has excellent chemical stability and can protect the material interface. Its good ductility can act as a buffer matrix to slow down the volume effect during charging and discharging, and its good conductivity can promote the migration of lithium ions.

[0006] CN104466135A discloses a method for coating a positive electrode material of lithium nickel cobalt manganese oxide with a conductive polymer, comprising the following steps: (1) preparing LiNi by mechanical activation; 1 / 3 Co 1 / 3 Mn 1 / 3 Precursor mixture; (2) to LiNi 1 / 3 Co 1 / 3 Mn 1 / 3Add an aqueous solution or organic solution of a conductive polymer to the precursor mixture; (3) spray dry the mixture prepared in step (2) to obtain a uniformly mixed precursor powder; (4) calcine the vibrated or compacted precursor powder and cool it to room temperature to obtain a conductive polymer-coated lithium nickel cobalt manganese oxide positive electrode material. However, the thermal decomposition temperature of a general conductive polymer is below 500°C. Moreover, this method makes it difficult to control the number average molecular weight of the synthesized conductive polymer, and the molecular weight distribution is relatively wide. If there are many oligomers in it, the conductivity of the conductive polymer will be greatly reduced.

[0007] Therefore, it is necessary to provide a new coated modified positive electrode material and a preparation method and application thereof, so that the coating layer thickness of the positive electrode material obtained by the preparation method is controllable and the structure is stable, and it has good rate performance and cycle performance. Summary of the invention

[0008] The object of the present invention is to provide a coated modified positive electrode material and a preparation method and application thereof. The surface of the coated modified positive electrode material is evenly coated and has structural stability during processing, excellent rate performance and cycle performance, and the surface of the coated modified positive electrode material has a low residual alkali content.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0011] The DA type conjugated polymer organic solution and the positive electrode material are mixed, and the organic solvent is removed to obtain the coated modified positive electrode material.

[0012] The DA type conjugated polymer has electron donating units (D units) and electron deficient units (A units) that appear alternately. The present invention uses the DA type conjugated polymer to coat and modify the positive electrode material, and can form a uniform and dense coating layer on the surface of the material, and the thickness of the coating layer is controllable; moreover, the DA type conjugated polymer has excellent chemical stability, and its good ductility can be used as a buffer matrix to slow down the volume effect of the charge and discharge process, and it also has good conductivity; the coated and modified positive electrode material of the present invention is used in a battery, which can make the battery have excellent rate performance and cycle performance.

[0013] Preferably, the D unit of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution comprises any one of a p-phenylene vinylene derivative, a thiophene derivative, a dithiophene derivative, a benzoterthiophene derivative or a fluorene derivative, or a combination of at least two thereof;

[0014] Preferably, the A unit of the DA type conjugated polymer includes any one or a combination of at least two of benzothiadiazole derivatives, pyridothiadiazole derivatives, pyrrolopyrroledione derivatives, benzothiadiazole derivatives, naphthalene diimide derivatives, quinoxaline derivatives, isoindigo derivatives or thienopyrroledione derivatives.

[0015] Preferably, the DA-type conjugated polymer includes any one or a combination of at least two of PPyT-ff (TT), PPyT-T or PST-BT. Typical but non-limiting combinations include a combination of PPyT-ff (TT) and PPyT-T, a combination of PPyT-T and PST-BT, a combination of PPyT-ff (TT) and PST-BT, or a combination of PPyT-ff (TT), PPyT-T and PST-BT, preferably PPyT-ff (TT).

[0016] Preferably, the number average molecular weight of the PPyT-ff(TT) is 60-90 kDa, for example, 60 kDa, 62 kDa, 65 kDa, 70 kDa, 75 kDa, 80 kDa, 85 kDa or 90 kDa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] Preferably, the organic solvent in the DA-type conjugated polymer organic solution includes any one of tetrahydrofuran, acetone, chloroform, toluene or chlorobenzene, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of tetrahydrofuran and acetone, a combination of chloroform and toluene, a combination of acetone and chlorobenzene, a combination of tetrahydrofuran, acetone and chloroform, a combination of acetone, chloroform, toluene and chlorobenzene, or a combination of tetrahydrofuran, acetone, chloroform, toluene and chlorobenzene.

[0018] Preferably, the concentration of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution is 1-5 g / L, for example, 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0019] Preferably, the solid-to-liquid ratio of the positive electrode material to the DA-type conjugated polymer organic solution is 1:(0.8-1.2), for example, it can be 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The unit of the solid-to-liquid ratio is g / mL.

[0020] Preferably, the method of removing the organic solvent comprises rotary evaporation.

[0021] Preferably, the temperature for removing the organic solvent is 100-300°C, for example, 100°C, 150°C, 200°C, 250°C or 300°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, the method for preparing the positive electrode material comprises the following steps:

[0023] (1) mixing a high nickel precursor and a lithium source, sintering in an oxygen atmosphere, and crushing to obtain a sintered material;

[0024] (2) washing the sintered material with water and drying it to obtain the positive electrode material;

[0025] The molar amount of nickel in the high-nickel precursor in step (1) is more than 70% of the total molar amount of metal in the high-nickel precursor, for example, it can be 70%, 75%, 80%, 85% or 90%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the sintering temperature in step (1) is 700-750°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C or 750°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] Preferably, the sintering time in step (1) is 10-14 h, for example, 10 h, 11 h, 12 h, 13 h or 14 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the particle size D50 of the sintered material in step (1) is 8-14 μm, for example, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm or 14 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the water-to-material ratio of the water washing in step (2) is (0.8-1.2):1, for example, it can be 0.8:1, 0.9:1, 1:1, 1.1:1 or 1.2:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the water washing temperature in step (2) is 24-27°C, for example, 24°C, 25°C, 26°C or 27°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the washing time in step (2) is 8-15 min, for example, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the water washing in step (2) is accompanied by stirring at 350-450 rpm, for example, 350 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm or 450 rpm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the drying temperature in step (2) is 80-120° C. and the drying time is 8-12 h.

[0034] The drying temperature in step (2) of the present invention is 80-120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] The drying time in step (2) of the present invention is 8-12 hours, for example, it can be 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] As a preferred technical solution of the preparation method described in the first aspect of the present invention, the preparation method comprises the following steps:

[0037] The positive electrode material and the DA type conjugated polymer organic solution are mixed at a solid-liquid ratio of 1: (0.8-1.2), and the organic solvent is removed by rotary evaporation at 100-300° C. to obtain the coated modified positive electrode material; the unit of the solid-liquid ratio is g / mL;

[0038] The concentration of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution is 1-5 g / L; the DA-type conjugated polymer is PPyT-ff (TT) with a number average molecular weight of 60-90 kDa;

[0039] The positive electrode material is prepared by the following method:

[0040] (1) mixing a high-nickel precursor and a lithium source, sintering in an oxygen atmosphere, and crushing to obtain a sintered material with a particle size D50 of 8-14 μm; the molar amount of nickel in the high-nickel precursor is more than 70% of the total molar amount of metal in the high-nickel precursor;

[0041] The sintering temperature is 700-750°C and the sintering time is 10-14h;

[0042] (2) washing the sintered material with water at 24-27° C. for 8-15 min, and drying at 80-120° C. for 8-12 h to obtain the positive electrode material; the water-to-material ratio of the water washing is (0.8-1.2):1; and the water washing is accompanied by stirring at 350-450 rpm.

[0043] In a second aspect, the present invention provides a coated modified positive electrode material, wherein the coated modified positive electrode material is obtained by the preparation method described in the first aspect.

[0044] In a third aspect, the present invention provides a battery, comprising the coated modified positive electrode material described in the second aspect.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The DA type conjugated polymer has electron donating units (D units) and electron deficient units (A units) that appear alternately. The present invention uses the DA type conjugated polymer to coat and modify the positive electrode material, and can form a uniform and dense coating layer on the surface of the material, and the thickness of the coating layer is controllable; moreover, the DA type conjugated polymer has excellent chemical stability, and its good ductility can be used as a buffer matrix to slow down the volume effect of the charge and discharge process, and it also has good conductivity; the coated and modified positive electrode material of the present invention is used in a battery, which can make the battery have excellent rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 A comparison chart of the rate performance of the coated modified positive electrode materials provided in Example 3 and Comparative Example 3;

[0048] Figure 2 This is a comparison chart of the cycle performance of the coated modified positive electrode materials provided in Example 3 and Comparative Example 3. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0050] Example 1

[0051] This embodiment provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0052] The positive electrode material and the DA-type conjugated polymer organic solution are mixed at a solid-liquid ratio of 1:1, and the organic solvent is removed by rotary evaporation at 200° C. to obtain the coated modified positive electrode material; the unit of the solid-liquid ratio is g / mL;

[0053] The organic solvent of the DA type conjugated polymer organic solution is tetrahydrofuran;

[0054] The concentration of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution is 1 g / L; the DA-type conjugated polymer is PPyT-ff (TT) with a number average molecular weight of 74 kDa;

[0055] The positive electrode material is prepared by the following method:

[0056] (1) Mixed Ni 0.88 Co 0.1 Al 0.02 (OH)2 and lithium hydroxide, wherein the molar amount of lithium hydroxide is 1.06 times the theoretical amount; sintering under an oxygen atmosphere, and crushing to obtain a sintered material with a particle size D50 of 10 μm;

[0057] The sintering temperature is 720°C and the sintering time is 12h;

[0058] (2) washing the sintered material with water at 25° C. for 10 min and drying it at 100° C. for 10 h to obtain the positive electrode material; the water-to-material ratio of the water washing is 1:1; and the water washing is accompanied by stirring at 400 rpm.

[0059] The BET specific surface area of ​​the positive electrode material obtained in this example is 1.08 m 2 / g, the total residual alkali on the surface is 0.34wt%, of which the content of LiOH is 0.16wt% of the positive electrode material, and the content of Li2CO3 is 0.18wt% of the positive electrode material.

[0060] Example 2

[0061] This embodiment provides a method for preparing a coated modified positive electrode material, which is the same as that of Embodiment 1 except that the concentration of the DA type conjugated polymer in the DA type conjugated polymer organic solution is 2 g / L.

[0062] Example 3

[0063] This embodiment provides a method for preparing a coated modified positive electrode material, which is the same as that of Embodiment 1 except that the concentration of the DA type conjugated polymer in the DA type conjugated polymer organic solution is 3 g / L.

[0064] Example 4

[0065] This embodiment provides a method for preparing a coated modified positive electrode material, which is the same as that of Embodiment 1 except that the concentration of the DA type conjugated polymer in the DA type conjugated polymer organic solution is 5 g / L.

[0066] Example 5

[0067] This embodiment provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0068] The positive electrode material and the DA-type conjugated polymer organic solution are mixed at a solid-liquid ratio of 1:0.8, and the organic solvent is removed by rotary evaporation at 100° C. to obtain the coated modified positive electrode material; the unit of the solid-liquid ratio is g / mL;

[0069] The organic solvent of the DA type conjugated polymer organic solution is toluene;

[0070] The concentration of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution is 1 g / L; the DA-type conjugated polymer is PPyT-ff (TT) with a number average molecular weight of 90 kDa;

[0071] The preparation method of the positive electrode material described in this embodiment is the same as that in Embodiment 1.

[0072] Example 6

[0073] This embodiment provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0074] The positive electrode material and the DA-type conjugated polymer organic solution are mixed at a solid-liquid ratio of 1:1.2, and the organic solvent is removed by rotary evaporation at 300° C. to obtain the coated modified positive electrode material; the unit of the solid-liquid ratio is g / mL;

[0075] The organic solvent of the DA type conjugated polymer organic solution is tetrahydrofuran;

[0076] The concentration of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution is 1 g / L; the DA-type conjugated polymer is PPyT-ff (TT) with a number average molecular weight of 60 kDa;

[0077] The preparation method of the positive electrode material described in this embodiment is the same as that in Embodiment 1.

[0078] Example 7

[0079] This embodiment provides a method for preparing a coated modified positive electrode material, which is the same as that of Example 1 except that the DA-type conjugated polymer of Example 1 is replaced by PST-BT with a number average molecular weight of 65 KDa.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0082] 500 g of the positive electrode material was uniformly mixed with 2.86 g of boric acid and heat treated at 200° C. for 6 h to obtain a coated modified positive electrode material.

[0083] The positive electrode material is the same as the positive electrode material in Example 1.

[0084] Comparative Example 2

[0085] This comparative example provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0086] 500 g of the positive electrode material was uniformly mixed with 4.29 g of boric acid and heat treated at 200° C. for 6 h to obtain a coated modified positive electrode material.

[0087] The positive electrode material is the same as the positive electrode material in Example 1.

[0088] Comparative Example 3

[0089] This comparative example provides a method for preparing a coated modified positive electrode material, the preparation method comprising the following steps:

[0090] 500 g of the positive electrode material was uniformly mixed with 1.42 g of aluminum oxide and heat treated at 500° C. for 6 h to obtain a coated modified positive electrode material.

[0091] The positive electrode material is the same as the positive electrode material in Example 1.

[0092] Performance Testing

[0093] (1) The BET specific surface area and the residual alkali content on the surface of the coated modified positive electrode materials provided in Examples 1-7 and Comparative Examples 1-3 were tested by potentiometric titration. The test results are shown in Table 1.

[0094] Table 1

[0095] <![CDATA[BET(m 2 / g)]]> Total residual alkali (wt%) LiOH (wt%) <![CDATA[Li2CO3(wt%)]]> Example 1 0.48 0.48 0.25 0.23 Example 2 0.39 0.41 0.22 0.19 Example 3 0.38 0.35 0.20 0.15 Example 4 0.35 0.27 0.15 0.12 Example 5 0.44 0.45 0.23 0.22 Example 6 0.45 0.45 0.23 0.22 Example 7 0.48 0.50 0.25 0.25 Comparative Example 1 0.43 0.49 0.25 0.24 Comparative Example 2 0.45 0.52 0.25 0.27 Comparative Example 3 0.40 0.58 0.28 0.30

[0096] As can be seen from Table 1, the preparation method provided by the present invention uses a DA-type conjugated polymer to coat the positive electrode material, which can effectively reduce the surface residual alkali content of the obtained coated modified positive electrode material.

[0097] (2) The coated modified positive electrode materials provided in Examples 1-6 and Comparative Examples 1-3 were assembled into lithium ion batteries. The assembly method was as follows: the coated modified positive electrode material was mixed with acetylene black, polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) (the mass ratio of the coated modified positive electrode material, acetylene black and PVDF was 96.9:1.5:1.6) to obtain a positive electrode slurry, and then the slurry was coated on an aluminum foil and dried to obtain a positive electrode plate. Finally, the positive electrode plate was assembled with an electrolyte (1 mol / L LiPF6 / EC+DMC+EMC (EC is ethylene carbonate, EMC is ethyl methyl carbonate, DMC is dimethyl carbonate, and the volume ratio of EC, DMC and EMC is 1:1:1)), a separator (polypropylene microporous membrane), and a negative electrode plate (lithium plate) to prepare a button battery. The first discharge specific capacity, first coulomb efficiency, cycle capacity retention rate and rate performance of the assembled lithium ion battery were tested;

[0098] The test method for the first charge-discharge specific capacity and the first coulombic efficiency is as follows: at 25°C, the obtained lithium-ion battery is charged to 4.25V at 0.2C, left to stand for 5 minutes, and then discharged to 2.5V at 0.2C to obtain its first charge capacity and first discharge capacity, and the first coulombic efficiency is calculated;

[0099] The testing method for the cycle capacity retention rate is as follows: at 25°C, the obtained lithium-ion battery is first charged to 4.25V at 0.2C, allowed to stand for 5 minutes, and then discharged to 2.5V at 0.2C. This process is repeated twice; then charged to 4.25V at 1.0C, allowed to stand for 5 minutes, and then discharged to 2.5V at 1.0C; this process is repeated 50 times to obtain its cycle capacity retention rate.

[0100] The test method for rate performance is as follows: the obtained lithium-ion battery is first charged and discharged once at 0.2C / 0.2C, then charged and discharged once at 0.5C / 0.5C, once at 0.5C / 1C, once at 0.5C / 2C, and once at 0.5C / 3C, and the ratio of each discharge capacity to the initial capacity (0.2C) is recorded.

[0101] The results are shown in Table 2 and Table 3.

[0102] Table 2

[0103]

[0104]

[0105] Table 3

[0106]

[0107]

[0108] Figure 1 A comparison chart of the rate performance of the coated modified positive electrode materials provided in Example 3 and Comparative Example 3; Figure 2 The cycle performance comparison diagram of the coated modified positive electrode material provided in Example 3 and Comparative Example 3; Figure 1 and Figure 2 It can be seen that the coated modified positive electrode material provided in the present application can make the coating layer on the surface of the positive electrode material dense and uniform through the use of DA-type conjugated polymer, and the polymer used has good conductivity, so that the rate performance and cycle performance of the embodiment are greatly improved compared with the comparative example.

[0109] As can be seen from Table 2, the preparation method provided by the present invention uses a DA-type conjugated polymer to coat the positive electrode material, which can improve the capacity and initial efficiency of the material to a certain extent.

[0110] It can be seen from Table 3 that the preparation method provided by the present invention uses a DA-type conjugated polymer to coat the positive electrode material, which can improve the rate performance of the material to a certain extent.

[0111] In summary, DA-type conjugated polymers have alternating electron-donating units (D units) and electron-deficient units (A units). The present invention uses DA-type conjugated polymers to coat and modify the positive electrode material, which can form a uniform and dense coating layer on the surface of the material, and the thickness of the coating layer is controllable; moreover, DA-type conjugated polymers have excellent chemical stability, and their good ductility can be used as a buffer matrix to slow down the volume effect of the charge and discharge process, and they also have good conductivity; using the coated and modified positive electrode material of the present invention for a battery can enable the battery to have excellent rate performance and cycle performance.

[0112] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a coated modified positive electrode material, characterized in that: The preparation method comprises the following steps: Mixing the DA-type conjugated polymer organic solution with the positive electrode material, removing the organic solvent, and obtaining the coated modified positive electrode material; The D unit of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution includes any one of a p-phenylene vinylene derivative, a thiophene derivative, a dithiophene derivative, a benzoterthiophene derivative or a fluorene derivative, or a combination of at least two thereof; The A unit of the DA type conjugated polymer includes any one or a combination of at least two of benzothiadiazole derivatives, pyridothiadiazole derivatives, pyrrolopyrroledione derivatives, benzothiadiazole derivatives, naphthalene diimide derivatives, quinoxaline derivatives, isoindigo derivatives or thienopyrroledione derivatives.

2. The preparation method according to claim 1, characterized in that: The DA type conjugated polymer includes any one of PPyT-ff(TT), PPyT-T or PST-BT or a combination of at least two thereof.

3. The preparation method according to claim 1, characterized in that: The DA type conjugated polymer is PPyT-ff(TT).

4. The preparation method according to claim 3, characterized in that: The number average molecular weight of the PPyT-ff(TT) is 60-90 kDa.

5. The preparation method according to claim 1, characterized in that: The organic solvent in the DA type conjugated polymer organic solution includes any one of tetrahydrofuran, acetone, chloroform, toluene or chlorobenzene, or a combination of at least two thereof.

6. The preparation method according to claim 1, characterized in that: The concentration of the DA type conjugated polymer in the DA type conjugated polymer organic solution is 1-5 g / L.

7. The preparation method according to claim 1, characterized in that: The solid-liquid ratio of the positive electrode material to the DA-type conjugated polymer organic solution is 1:(0.8-1.2), and the unit of the solid-liquid ratio is g / mL.

8. The preparation method according to claim 1, characterized in that: The method of removing the organic solvent includes rotary evaporation.

9. The preparation method according to claim 1, characterized in that: The temperature for removing the organic solvent is 100-300°C.

10. The preparation method according to claim 1, characterized in that: The preparation method of the positive electrode material comprises the following steps: (1) mixing a high nickel precursor and a lithium source, sintering in an oxygen atmosphere, and crushing to obtain a sintered material; (2) washing the sintered material with water and drying it to obtain the positive electrode material; The molar amount of nickel in the high-nickel precursor in step (1) is more than 70% of the total molar amount of metal in the high-nickel precursor.

11. The preparation method according to claim 10, characterized in that: The sintering temperature in step (1) is 700-750°C.

12. The preparation method according to claim 10, characterized in that: The sintering time in step (1) is 10-14 hours.

13. The preparation method according to claim 10, characterized in that: The particle size D50 of the sintered material in step (1) is 8-14 μm.

14. The preparation method according to claim 10, characterized in that: The water-to-material ratio of the water washing in step (2) is (0.8-1.2):

1.

15. The preparation method according to claim 10, characterized in that: The water washing temperature in step (2) is 24-27°C.

16. The preparation method according to claim 10, characterized in that: The washing time in step (2) is 8-15 minutes.

17. The preparation method according to claim 10, characterized in that: The water washing in step (2) is accompanied by stirring at 350-450 rpm.

18. The preparation method according to claim 10, characterized in that: The drying temperature in step (2) is 80-120° C. and the drying time is 8-12 hours.

19. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: The positive electrode material and the DA type conjugated polymer organic solution are mixed at a solid-liquid ratio of 1: (0.8-1.2), and the organic solvent is removed by rotary evaporation at 100-300° C. to obtain the coated modified positive electrode material; the unit of the solid-liquid ratio is g / mL; The concentration of the DA-type conjugated polymer in the DA-type conjugated polymer organic solution is 1-5 g / L; the DA-type conjugated polymer is PPyT-ff (TT) with a number average molecular weight of 60-90 kDa; The positive electrode material is prepared by the following method: (1) mixing a high-nickel precursor and a lithium source, sintering in an oxygen atmosphere, and crushing to obtain a sintered material with a particle size D50 of 8-14 μm; the molar amount of nickel in the high-nickel precursor is more than 70% of the total molar amount of metal in the high-nickel precursor; The sintering temperature is 700-750°C and the sintering time is 10-14h; (2) washing the sintered material with water at 24-27° C. for 8-15 min, and drying at 80-120° C. for 8-12 h to obtain the positive electrode material; the water-to-material ratio of the water washing is (0.8-1.2):1; and the water washing is accompanied by stirring at 350-450 rpm.

20. A coated modified positive electrode material, characterized in that: The coated modified positive electrode material is obtained by the preparation method described in any one of claims 1-19.

21. A battery, characterized in that: The battery comprises the coated modified positive electrode material as claimed in claim 20.

Citation Information

Patent Citations

  • Method for coating conductive polymer on Ni-Co-Mn acid lithium positive electrode material

    CN104466135A

  • Conjugated polymers containing pyridalthiadiazole-benzodithiophene, preparing method thereof and applications thereof

    CN103936968A

  • Lithium battery electrode preparation method including polymer material with stable interface and application of lithium battery electrode in solid lithium battery

    CN105702919A